Avery's diseases of the newborn - Gleason, Christine A; Juul, Sandra E (Elsevier, 2018)
Covering the evaluation and management of every key disease and condition affecting newborns, Avery’s Diseases of the Newborn, remains your source for practical, clinically relevant information in this fast-changing field. Nakladatelská anotace. Kráceno
Keywords: nemoci novorozenců; perinatální péče; Perinatal Care; pediatrie; Pediatrics; Infant, Newborn, Diseases; neonatologie; Neonatology; perinatologie a neonatologie